Molecular and functional genetics of the proopiomelanocortin gene, food intake regulation and obesity. Issue 17 (20th August 2017) - Rubinstein, Marcelo; Low, Malcolm J.
Abstract : A specter is haunting the world, the specter of obesity. During the last decade, this pandemia has skyrocketed threatening children, adolescents and lower income families worldwide. Although driven by an increase in the consumption of ultraprocessed edibles of poor nutritional value, the obesogenic changes in contemporary human lifestyle affect people differently, revealing that some individuals are more prone to develop increased adiposity. During the last years, we performed a variety of genetic, evolutionary, biochemical and behavioral experiments that allowed us to understand how a group of neurons present in the arcuate nucleus of the hypothalamus regulate the expression of the proopiomelanocortin ( Pomc ) gene and induce satiety. We disentangled the neuronal transcriptional code of Pomc by identifying the cis ‐acting regulatory elements and primary transcription factors controlling hypothalamic Pomc expression and determined their functional importance in the regulation of food intake and adiposity. Altogether, our studies reviewed here shed light on the power and limitations of the mammalian central satiety pathways and may contribute to the development of individual and collective strategies to reduce the debilitating effects of the self‐induced obesity pandemia. Abstract :